2016
DOI: 10.9721/kjfst.2016.48.6.536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freezing-storage temperature on the shelf life of mackerel fish

Abstract: The purpose of this study was to evaluate changes in the quality characteristics of mackerel fish fillet under freezing storage conditions. The changes in product quality were determined by measuring pH, volatile basic nitrogen (VBN); thiobarbituric acid (TBA), lightness (L*), redness (a*), yellowness (b*) values, shearing force, and microbiological evaluation (Total Plate Count, TPC) during 21 days of storage at −20, −5, and −1 o C, and their shelf-lives were established. TPC as an effective quality indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The TBARS levels of sh stored in the refrigerated treatment were higher than those of the other groups after 9 days of storage. Hydroperoxide, which is the primary product generated by oxidation of fat and produced by microbial metabolism and lipolytic enzymes, is more easily developed during refrigerated treatment (Joo et al, 2016). In this study, the TBARS values of refrigerated salmon and olive ounder increased more sharply than those of samples stored under the supercooled treatment.…”
Section: Tbarsmentioning
confidence: 59%
“…The TBARS levels of sh stored in the refrigerated treatment were higher than those of the other groups after 9 days of storage. Hydroperoxide, which is the primary product generated by oxidation of fat and produced by microbial metabolism and lipolytic enzymes, is more easily developed during refrigerated treatment (Joo et al, 2016). In this study, the TBARS values of refrigerated salmon and olive ounder increased more sharply than those of samples stored under the supercooled treatment.…”
Section: Tbarsmentioning
confidence: 59%
“…It is considered that the reaction of samples stored at a temperature below −50°C results in less base nitrogen content attributed to the oxidation of lipid components, such as phospholipids, and lowgrade basic substances, such as trimethylamine produced by the reduction of trimethylamine N-oxide and materials such as ammonia nitrogen, generated by protein degradation due to bacterial growth. [25,50] Additionally, Tolsotrebrov et al [19] reported that absolute stabilization of protein at deep-freezing temperatures (below −70°C) is better than that at relatively high temperatures. Furthermore, when stored at deep-freezing temperatures, it is difficult to correct the reaction due to the lack of water molecules, which could restrain the rising values of TVBN.…”
Section: A-cmentioning
confidence: 99%
“…[21][22][23] Several studies involving the long-term storage of fish frozen at-18°C have also been conducted. [24,25] Therefore, studies involving the storage of fishes at deep-freezing temperatures (<−50°C) for long-term periods are needed. Moreover, despite the many advantages of storing food products at deep-freezing temperatures, consumers rarely have access to a deep freezer due to economical and validity factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is an emerging consumer demand for storing meat and fish at temperatures above typical freezer levels (-20℃) and below refrigerator temperatures (4℃) for home use (Joo et al, 2016). While extensive research exists on the storage conditions for meat and fish (Joo et al, 2016;Kim and Moon, 1998;Lee et al, 2003), studies on the storage temperature and duration for alternative foods are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…There is an emerging consumer demand for storing meat and fish at temperatures above typical freezer levels (-20℃) and below refrigerator temperatures (4℃) for home use (Joo et al, 2016). While extensive research exists on the storage conditions for meat and fish (Joo et al, 2016;Kim and Moon, 1998;Lee et al, 2003), studies on the storage temperature and duration for alternative foods are scarce. This study investigates the impact of storage temperature on the structural properties of TVP after production, aiming to provide insights into its distribution and consumption lifespan, as well as offering foundational data for manufacturers and distributors.…”
Section: Introductionmentioning
confidence: 99%